A Randomized Trial of Hospital Vs Home Self Administration of Vaginal Misoprostol for Medical Abortion - Shrestha, A; Sedhai, LB (Kathmandu University Medical Journal, 2015)
Background A combination of mifepristone followed after 24 hrs by misoprostol has proved a safe and effective abortifacient for termination of early pregnancy. Home use of misoprostol for medical abortion is still controversial in many countries including ours where women’s literacy rate is low. Particularly in developing countries, this method markedly decreased the hospital visit which would be beneficial to patients and hospital staff. Objective To see whether the home self administration of vaginal misoprostol was equally effective as administered by trained staff in terms of successful termination of early pregnancy. Secondary outcomes were bleeding and pain duration during medical abortion, side effects, reason for termination of pregnancy and women’s acceptability of the procedure. Method One hundred and eighty eight women requesting medical abortion with pregnancy less than 63 days gestation were randomized into two groups either self administration of vaginal misoprostol (800 mcg) at home or hospital administration 24 hours after oral 200 mg mifepristone. Ultrasound was performed after 14 days to confirm complete abortion. Result The overall success rate was similar in two groups: 89.13% on home group Vs 86.9% in hospital group. Eleven out of 18 women (61.1%) having incomplete abortion had successful termination after 2nd dose misoprostol( 400 mcg). None of the women had continued pregnancy. Multigravida had slightly higher risk of failure (R.R: 1.04). Conclusion Home self administration of vaginal misoprostol was safe and effective for early termination of medical abortion and was acceptable. Use of extra dose of misoprostol has advantage of higher completion rate of abortion. Kathmandu University Medical Journal Vol.12(3) 2014; 185-189